Distribution and Ethnobotanical Significance of Araceae Family Plants in Upper Assam, India - Sinha, Darshita; Borkataky, Munmi (Ethnobotany Research and Applications, 2025)
Background: Aroids are a diverse group of plants under the Araceae family with ecological and ethnobotanical significance. Their potential for addressing food security and sustainable development remains underutilized due to the presence of antinutritional factors and limited public awareness. This study aims to document the distribution, traditional uses, and ecological roles of Aroids found in Upper Assam. Methods: Field surveys were conducted from January 2022 to April 2024 across seven districts of Upper Assam. Data on local names, plant parts used, and ethnomedicinal applications were collected. Plant species were photographed, voucher specimens were collected, identified by experts and submitted to the herbarium at Dibrugarh University for future reference. Results: The study identified 46 species of aroid belonging to 19 genera, which is categorized into cultivated, wild, and ornamental types. Ethnobotanical data showed diverse uses, including treatments of ailments and applications as famine food during environmental challenges like floods. Morphological variations in leaf structure and corm shapes provided an understanding of species diversity. Colocasia sp. and Xanthosoma sp. were found to be represented by highest number of species. Despite their significant nutritional and medicinal value, antinutritional factors remain a challenge, limiting broader acceptance. Conclusion: Aroids play a crucial role in supporting biodiversity, cultural heritage, food and nutritional security in Upper Assam, offering a resilient solution to food security challenges. This study highlights the need for conservation, public awareness, and sustainable utilization to unlock their full potential for addressing global challenges and contribute to the growing understanding of aroids' role in traditional knowledge systems, highlighting their potential for sustainable food and medicinal resource development. Keywords: Aroids, Araceae, Ethnobotanical, Ecological Distribution, Food Security, Ethnomedicine